2022
DOI: 10.22219/jpbi.v8i2.20732
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive skill profile of biology education students at institute of teachers’ education in South Sulawesi, Indonesia

Abstract: Metacognitive skills are one of the abilities required in the twenty-first century, to achieve independent learning. However, these skills still need to review whether these skills have been empowered by educators, particularly in universities. This research was aimed at determining the metacognitive skill profile of Biology Education students at the Institute of Teachers’ Education in South Sulawesi, Indonesia. This research used a descriptive quantitative method. The population of this research was all the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Other research conducted by Kristiani et al [53] reported that metacognitive skills and scientific attitudes significantly contribute to students' academic achievement. Furthermore, Adiansyah et al [54] also stated that metacognitive skills and motivation significantly contribute to students' retention in biology learning.…”
Section: Discussionmentioning
confidence: 99%
“…Other research conducted by Kristiani et al [53] reported that metacognitive skills and scientific attitudes significantly contribute to students' academic achievement. Furthermore, Adiansyah et al [54] also stated that metacognitive skills and motivation significantly contribute to students' retention in biology learning.…”
Section: Discussionmentioning
confidence: 99%
“…Hal ini yang mendasari dalam perencanaan penggunaan strategi pembelajaran terbaru agar siswa SMK jurusan kesehatan di SMK muhammadiyah 3 wates dapat meningkat pengetahuan metakognitifnya. Upaya peningkatan keterampilan metakognitif tersebut dapat dilakukan melalui pelatihan keterampilan metakognitif dan penerapan strategi dan model pembelajaran yang kreatif, inovatif dan kolaboratif pembelajaran kolaboratif (Adiansyah et al 2022;Kuhn, 2020;Kuhn et al 2015)…”
Section: Pembahasanunclassified
“…Therefore, both PBL and RQA models are considered appropriate to be applied in learning strategies with a constructivist approach. These two models are not only based on the skill of memorizing concepts or facts but the process of interaction between students and their learning environment [43]. PBLRQA can be used in developing students' future life skills.…”
Section: Introductionmentioning
confidence: 99%